Preeclampsia, prematurity and cardiovascular health in adult life - Lewandowski, A; Leeson, C (Elsevier, 2014)
Investigations into how perinatal growth and intrauterine environment may 'programme' risk of later cardiovascular disease have been ongoing for over two decades. One of the more recent outcomes of these studies is the observation that certain pregnancy-related conditions, such as preterm birth, have an unusually large impact on the long-term cardiovascular health of the offspring. In the present paper, we review the current literature of how preterm birth affects the long-term cardiovascular structure and function of the offspring, considering three major areas of investigation: firstly, outlining the long-term cardiovascular phenotypic changes in preterm-born individuals; secondly, investigating factors related to preterm birth that may be modifying cardiovascular phenotype, such as preeclampsia, perinatal interventions, and physiological disturbances; and thirdly, the expected clinical relevance of these cardiovascular changes. This review discusses the importance of continued research focused on the mechanistic understanding of these cardiovascular alterations in order to develop specific primary prevention strategies.